Heterostructure NaGdF4:Yb, Er anchored on MIL-101 for promoting photoelectronic response and photocatalytic activity. Issue 47 (22nd November 2019) - Lv, Baize; Jiao, Jiqing; Liu, Yi; Liu, Lihua; Zhang, Jiyun; Li, Yao; Wang, Jiuxing; Tang, Jianguo
Abstract : Fabrication of heterostructure MIL-101/NaGdF4 :Yb, Er for tuning the fluorescence and improving the photocatalytic activity of the composites. Abstract : Herein, NaGdF4 :Yb, Er nanoparticles were anchored on a Material of Institute Lavoisier (MIL-101). In the well-defined heterostructure, MIL-101/NaGdF4 :Yb, Er, the absorption and fluorescence could be tuned, and the composite facilitated the separation of photogenerated electron–hole pairs. Moreover, the heterostructure displayed a higher photocurrent and better degradation ability for Rhodamine B that its individual components owing to its synergistic effect.